Movement and manual therapy for adults with arthritis: 2012 National Health Interview Survey. (April 2018) - Pure, Elise; Terhorst, Lauren; Baker, Nancy
Highlights: Individuals with arthritis using movement therapy report a greater increase in emotional/physical wellbeing than with manual therapy use. People who are physically active are more likely to use movement and manually based CAMs. Women with arthritis are much more likely to use CAMs than are males. Minorities are underrepresented among users of both manual and movement therapies. Abstract: Background: The use of manual therapies (chiropractic manipulation, massage) and movement therapies (yoga, tai chi) by people with arthritis may relate to their personal characteristics, and the reported emotional and physical health outcomes may differ by type of therapy. Objectives: To describe personal characteristics and predictors of manual and movement therapy use for people with arthritis, and to compare the use of manual versus movement therapy to improve physical and emotional health outcomes for people with arthritis. Methodology: CAM respondents with arthritis were identified from the 2012 National Health Interview Survey (n = 8229). Data were analyzed to determine the overall percentages of CAM users, and to examine the associations between use/nonuse using multivariable linear regressions. Results: White, well-educated, physically active females were more likely to use both types of therapy. Movement therapy users reported positive emotional health outcomes twice as much as manual therapy users and 10% more reported positive physical health outcomes. Conclusion: While both movement and manual therapies can have positive effects on people with arthritis, it appears that active therapies are more beneficial than passive therapies.